Electron Microburst Size Distribution Derived With AeroCube‐6. Issue 3 (5th March 2020) - Shumko, M.; Johnson, A. T.; Sample, J. G.; Griffith, B. A.; Turner, D. L.; O'Brien, T. P.; Agapitov, O.; Blake, J. B.; Claudepierre, S. G.
Abstract: Microbursts are an impulsive increase of electrons from the radiation belts into the atmosphere and have been directly observed in low Earth orbit and the upper atmosphere. Prior work has estimated that microbursts are capable of rapidly depleting the radiation belt electrons on the order of a day; hence, their role to radiation belt electron losses must be considered. Losses due to microbursts are not well constrained, and more work is necessary to accurately quantify their contribution as a loss process. To address this question, we present a statistical study of > 35 keV microburst sizes using the pair of AeroCube‐6 CubeSats. The microburst size distribution in low Earth orbit and the magnetic equator was derived using both spacecraft. In low Earth orbit, the majority of microbursts were observed, while the AeroCube‐6 separation was less than a few tens of kilometers, mostly in latitude. To account for the statistical effects of random microburst locations and sizes, Monte Carlo and analytic models were developed to test hypothesized microburst size distributions. A family of microburst size distributions were tested, and a Markov chain Monte Carlo sampler was used to estimate the optimal distribution of model parameters. Finally, a majority of observed microbursts map to sizes less than 200 km at the magnetic equator. Since microbursts are widely believed to be generated by scattering of radiation belt electrons by whistler mode waves, the observed microburst size distribution was compared to whistler mode chorus size distributions derived in prior literature. Plain Language Summary: Electron microbursts are a subsecond, impulsive form of electron precipitation from the radiation environment right above Earth's atmosphere. Microbursts are believed to cause significant loss of electrons on the order of a day from the near‐Earth radiation belt environment. To make these estimates, researchers need to make simplifying assumptions that reduce the accuracy of loss estimates by an unknown amount, and it is necessary to understand these assumptions. This paper focuses on one assumption needed to calculate how many electrons are lost per microburst—the physical size of microbursts. This study is achieved by using a pair of AeroCube‐6 CubeSats that are orbiting a few hundred kilometers above Earth's surface. We find that most microbursts have a size less than a few tens of kilometers and some are as large as 100 km at AeroCube‐6's altitude. Furthermore, we found that small microbursts also correspond to a very small region where microbursts are believed to be generated in the heart of the radiation belts. Key Points: The dual AeroCube‐6 CubeSats simultaneously observed > 35 keV microbursts at a variety of spatial separations ranging from 2 to 100 km In low Earth orbit the majority of microbursts have a size on the order of a few tens of km Mapped to the magnetic equator, the majority of microbursts are less than 200 km in size, corresponding to the size of chorus wave packets